Effect of petcoke on the physical-chemical properties of lignite under microwave pyrolysis and its moisture re-adsorption capacity. (15th August 2019) - Ren, Yangguang; Zheng, Jiaxing; Xu, Zhiqiang; Zhang, Yuxing; Cao, Zhenning
Highlights: 10 wt% PC addition was most effective to facilitate the pyrolysis of lignite. The coal quality improved and the oxygen-containing functional groups decreased remarkably. The specific surface area and pore volume increased, the average pore diameter declined. The moisture re-adsorption capacity was effectively weakened under the synergy effects of the physical-chemical properties. A moisture re-adsorption ratio (MRR) model was built through multiple nonlinear regressions. Abstract: To remarkably weaken the moisture re-adsorption capacity of lignite through improving the physical-chemical properties, different additions of petcoke (PC) were used to promote the microwave pyrolysis of lignite. And then the physical-chemical property changes of upgraded lignite (UL) were investigated through X-ray photoelectron spectra (XPS), a Zeta potential analyzer, and low temperature N2 adsorption method. The results showed that: the coal quality improved, the oxygen-containing functional groups reduced significantly, the polarity of the surface became less negative, the specific surface area and pore volume increased, the average pore diameter declined, and the macropores converted to mesopores and micropores. Furthermore, these changes of UL reached their maximum when 10 wt% PC was added to promote microwave pyrolysis. The moisture re-adsorption behavior was prevented under the synergy effects of the physical-chemical structure such that the moisture re-adsorption ratio (MRR) decreased most with 10 wt% PC addition. An MRR model built through multiple nonlinear regressions proved appropriate to quantify and predict the moisture re-adsorption capacity of the UL.